Overall indexes of coordination in front crawl swimming - Mezêncio, B.; Pinho, J. P.; Huebner, R.; Vilas-Boas, J. P.; Amadio, A. C.; Serrão, J. C. (Journal of Sports Sciences, 2020)
The aim of this study was to propose a group of parameters able to quantify not only arm coordination but also inter limb coordination. These include the well know index of coordination with the relative duration of the stroke phases and two new parameters: the Index of synchronization (Ids) between arms and legs actions; and the Index of inter limb coordination (IdIC) calculated as the relative foot position during successive arm stroke phases. These parameters were compared between experts and amateur swimmers in a maximal front crawl sprint. The influence of arm stroke in leg kick parameters was also assessed, comparing the full stroke condition with a condition without arms actions. Sixty-five per cent of expert swimmers used synchronized limb actions while 95% of amateur swimmers used non-synchronized limb motions. These synchronized expert swimmers also converged towards a specific coordination pattern between foot position and arm stroke phases. In the condition without arms, both groups changed kick rate and amplitude. The present study reveals the interdependency of arms and legs actions and the importance of coordination and synchronization between limbs. Therefore, the proposed group of overall indexes of coordination provides a more complete marker for the analysis of swimming technique.